Implementasi Pembelajaran Jarak Jauh melalui Metode E-learning pada Pusat Pendidikan dan Pelatihan Teknis Fungsional Pertahanan Badiklat Kemhan - Asep Ridwan (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
Distance learning through the e-learning method is a learning process that is carried out online or digitally. This needs to be applied/implemented at the Defense Functional Technical Education and Training Center of the Ministry of Defense's Badiklat because of the demands of technological and information developments since the onset of Covid 19. The aim of this research is to understand the extent of the effectiveness of long-distance training using the e-Learning method at the Defense Functional Technical Training Center of the Ministry of Defense's Badiklat . The method used is descriptive qualitative, namely a case study approach which is intended to describe the perceptions of organizers and participants regarding the application of e-Learning learning methods in Group III Transfer Technical Training and Kindergarten General Administration Technical Training. III which was held in 2020. From the results of the analysis it was concluded that the interactivity aspect between Widyaiswara and the participants, both synchronously and asynchronously, had not taken place effectively. As for the aspect of independence in learning, in general the participants were quite enthusiastic and able to carry out learning activities independently. Furthermore, the accessibility aspect of e-Learning applications in general, both Widyaiswara and participants can access them well. Likewise, from the enrichment aspect, in general enrichment learning materials are quite good, such as providing presentation slides for training materials and teaching materials. As for video streaming, video tutorials, simulations and animations, they cannot yet be implemented, because the features in the e-Learning application are still limited. The results of this research show that most of the recommendations and suggestions are the need for additional features in e-Learning applications such as video conferencing, video streaming or video tutorials and other features to support the quality of interaction. Apart from that, there is also a need to increase the capacity of Widyaiswara regarding the use and utilization of information technology in the field of online/digital learning. And it is necessary to accelerate in supporting digitalization transformation in the field of education and training.